Knowledge, attitudes and practices in paediatricpediatric concussion: informing research, education and clinical care. Issue 11 (25th May 2017) - Provvidenza, Christine; Greenspoon, Dayna; Fait, Phil; Reed, Nick
Abstract : Objective: To assess knowledge, attitudes, and practices surrounding research, education and clinical care in paediatric concussion at One Voice: the 1st International Symposium on Paediatric Concussion. Design: Quantitative, cross sectional, one-group survey design. Setting: One Voice: the 1st International Symposium on Paediatric Concussion. Participants: Sixty-two international paediatric concussion leaders representing a multi-stakeholder group. Intervention: None. Outcome measures: A survey was designed to assess self-reported knowledge, attitudes, and practices surrounding paediatric concussion research, education, and clinical care. Main results: Participants identified knowledge gaps as an issue across different groups including athletes and coaches. Attitude towards concussion in the sport culture was recognised as a barrier to common issues such as under reporting and playing while symptomatic. Stakeholders also identified that healthcare professionals do not have adequate training to diagnose and manage paediatric concussion, and highlighted the need for additional knowledge and streamlined education to enhance clinical practices. Conclusions: Knowledge, attitude and practice gaps in paediatric concussion exist across various stakeholder groups, leading to inconsistencies in concussion care and a lack of concussion recognition and reporting. Survey results align with outcomes identified in the literature. One Voice stakeholders underscored the value of education in enhancing knowledge, and its role in shifting attitude and optimising practices in paediatric concussion: identification, management and prevention. These outcomes will inform research, education and clinical initiatives to best meet the needs of the paediatric concussion community. Competing interests: None.